2016
DOI: 10.1016/j.eneco.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Kansas farm managers to produce alternative cellulosic biofuel feedstocks: An analysis of adoption and initial acreage allocation

Abstract: This paper examines the likelihood that farm managers would be willing to harvest crop residue, or grow a dedicated annual or perennial bioenergy crop. In addition, factors affecting how many initial acres adopters would be willing to plant of a dedicated annual or perennial bioenergy crop are assessed. The study finds several factors affect farm managers' decisions to harvest crop residue, or grow annual or perennial bioenergy crops, as well as their potential initial acreage allocation decisions. These facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 33 publications
(58 reference statements)
4
24
2
Order By: Relevance
“…One such policy we suggest, given the controlling role of farm size on farmers' perceptions of marginal land availability, is to target large farm owners and operators to encourage bioenergy crop adoption. Such a recommendation is consistent with previous theoretical and empirical analysis (Khanna et al, 2017; Lynes et al, 2016). Larger farms are also expected to be more willing to adopt bioenergy crops because of the economy of scale (larger farm size compensates the usually high fixed cost of bioenergy crop production; Khanna et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…One such policy we suggest, given the controlling role of farm size on farmers' perceptions of marginal land availability, is to target large farm owners and operators to encourage bioenergy crop adoption. Such a recommendation is consistent with previous theoretical and empirical analysis (Khanna et al, 2017; Lynes et al, 2016). Larger farms are also expected to be more willing to adopt bioenergy crops because of the economy of scale (larger farm size compensates the usually high fixed cost of bioenergy crop production; Khanna et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Various farmer characteristics that have consistently been associated with a higher propensity to grow bioenergy crops include lower age, higher education levels, prior knowledge of bioenergy crops, use of alternative fuels, lower risk aversion, and less present-biasedness (Jiang et al, 2018;Khanna et al, 2017;Lynes et al, 2016;Mattia et al, 2018;Mooney et al, 2015;Qualls et al, 2012;Skevas et al, 2018;Swinton et al, 2017). Off-farm income has been shown to increase the willingness to supply bioenergy crops (Jensen et al, 2007;Qualls et al, 2012;Smith et al, 2018).…”
Section: Incentives For Converting Marginal Land To Bioenergy Cropsmentioning
confidence: 99%
“…Off-farm income has been shown to increase the willingness to supply bioenergy crops (Jensen et al, 2007;Qualls et al, 2012;Smith et al, 2018). Farm characteristics such as larger farms, higher percentage of farm leased, higher percentage of land in CRP, more marginal land, land already in a perennial land use such as hay, and the distance to bioenergy pellet facilities also contribute to a greater probability of bioenergy crop production (Jiang et al, 2018(Jiang et al, , 2019Lynes et al, 2016). For a comprehensive meta-analysis of the farmer characteristics that influence willingness to produce bioenergy crops, see Galik (2015).…”
Section: Incentives For Converting Marginal Land To Bioenergy Cropsmentioning
confidence: 99%
“…Among western U.S. farmers, Embaye et al [16] found that about 58% were interested in growing oilseeds for bioenergy feedstock. Lynes et al [19] found that 61% of the Kansas farmers surveyed would be willing to grow annual bioenergy feedstock crops such as sweet sorghum, while 44% would grow perennial bioenergy crops such as switchgrass. Jensen et al [17] found that about 30% of Tennessee farmers surveyed were interested in growing the perennial switchgrass.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from several studies have suggested that farmer demographics such as age and education level may influence interest in growing dedicated energy crops [16][17][18][19]. Most studies have found positive effects of higher education, however, findings regarding the effects of age on willingness to grow bioenergy feedstock crops have been mixed.…”
Section: Introductionmentioning
confidence: 99%